P110 ACCIDENTAL FINDING OF COR TRIATRIUM SINISTER IN AN ADULT: DIAGNOSIS MANAGMENT. (18th May 2022) - Talarico, M; Renne, S; Colangelo, M; Rizzuti, G; Talarico, R; Ceravolo, R
Abstract: A 45–year old woman presented at the emergency department for palpitations and fever. The EKG, thoracic x–ray and troponins were normal, only a neutrophil leucocytosis was found. The echocardiography showed a normal bi–ventricular and valvular function and a mobile, linear, mass in the left atrium. In order to exclude an infective vegetation the patient underwent to a 2D and 3D transesophageal echocardiography (Figure 1 and 2 ) which showed a left ventricle concentric remodelling (iLVmass 62 g/m2; RWT 0.45), preserved left and right ventricle function (LVEF according to Simpson 70%; FAC 50%) and valves function; inter–atrial septum defects were excluded, too. The mass was described as a mobile membrane in the left atrium at 2.11 cm from the mitral valve anular plane, which divided the atrium into two separate chambers with a large fenestration without trans–mitralic flow obstruction, supporting a cor triatrium sinister. We excluded endocarditis (the blood cultures were negative, too) and supra–valvular mitral ring (since the left appendage position in the antero–inferior side of the left atrium). The cardiac MRI showed (Figure 3 ) (SSFP–FIESTA, IR–GRE T1, STIR T2) confirmed the finding of a left atrium divided in two chamber by a iso–intense membraine from the coumadin ridge between the left upper pulmonary vein and the left appendage to the inter–atrial septum fossa ovalis, incomplete in the infero–lateral part. Venous drenaige and other congenital abnormalities were excluded. Miocarditis was excluded since no fibrosis in IR–GRE T1 and no edema in Triple T2 sequences. Since the non–obstructive cor triatrium sinister, grading IA according the Lucas classification, was confirmed, no surgical treatment was proposed and the patient was discharged without complications.